Die stil van my verlange na God: Oor Johann Wihelm Herrmann se verstaan van die ervaring van God - Veldsman, D. P. (Verbum et ecclesia, 1996)
Quenching my thirst for God: On Johann Wilhelm Herrmann's understanding of the experience of God This article, which is divided into two parts, focusses on the concept of the "experience of God" as understood by the German systematic theologian Wilhelm Herrmann (1846 - 1922) of Marburg in his "Der Verkehr des Christen mit Gott" (1886). The first part of the article explains the historical and theological context of Herrmann's "Der Verkehr ... n as well as the theological frontiers over against which he responded in his understanding of the experience of God. For Herrmann, this experience can not be justified by means of historical investigation. Neither is this experience a "holding for true" of doctrines nor has it its origin in humans themselves, but is rather a "search-find-experience" of the overwhelming "image of Jesus" in God's revelatory engagement with humanity. If, and only if, we search for the gracious God wholeheartedly, can he himself be found and not one or other doctrine or gift of God. The second part of the article elaborates on this "search-find-experience" by humans of God as understood by Herrmann, and indicates the influence it had on Herrmann's two greatest pupils, namely Karl Barth and Rudolf Bultmann. It is argued that Herrmann's understanding of the experience of God makes up the kernel of their theological vantage points, and in this respect, is critically evaluated.